2004
DOI: 10.1023/b:pham.0000022408.91151.64
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Prediction of Moisture-Mediated Dissolution Stability for Benazepril Hydrochloride Tablets

Abstract: Physical changes of tablets mediated by moisture were the main cause for reduction in dissolution. Inclusion of desiccant, although beneficial, cannot prevent reduction in dissolution completely. The simple physical model proposed in this report was found to be useful in predicting the dissolution stability of the dosage form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Haque and Roos (2006) recently speculated that freeze-dried (FD) materials might have a higher amount of hydrogen bonding sites available for water molecules in sorption than spray-dried (SD) materials. Indeed, even a small increase in moisture content of a drug above a critical value of 3% was shown to significantly decrease its dissolution rate (Li, Wei, Fleres, Comfort, & Royce, 2004). Consequently, a less exothermic response due to either higher moisture content of the powder, or a reduced number of available hydrogen bonding sites, could have major implications in the wetting mechanism and kinetics of food powders, which in turn might slow down their dissolution process.…”
Section: Introductionmentioning
confidence: 99%
“…Haque and Roos (2006) recently speculated that freeze-dried (FD) materials might have a higher amount of hydrogen bonding sites available for water molecules in sorption than spray-dried (SD) materials. Indeed, even a small increase in moisture content of a drug above a critical value of 3% was shown to significantly decrease its dissolution rate (Li, Wei, Fleres, Comfort, & Royce, 2004). Consequently, a less exothermic response due to either higher moisture content of the powder, or a reduced number of available hydrogen bonding sites, could have major implications in the wetting mechanism and kinetics of food powders, which in turn might slow down their dissolution process.…”
Section: Introductionmentioning
confidence: 99%
“…Water affected tablet dissolution by its interaction with APIs or excipients, as well as the tablet's porosity and mechanical strength. 44,45 A recent study by Okada et al showed that the sprayed water droplet had different evaporation rate, and the low drying air temperature would result in the spread of unevaporated droplets throughout the drying tower. 46 The presence of water will produce dry and wet phases in the powder.…”
Section: Multivariate Analysis Of Existing Data On Factors Affecting mentioning
confidence: 99%
“…The absorption of moisture can affect the properties of the powders used in pharmaceutical processing, such as compaction, blending, bulk density and flow [2][3][4][5]. For some drugs taken as oral solids, absorbed water can affect dissolution, disintegration and chemical stability [6][7][8][9][10]. Water has a wide-ranging impact on physical and chemical properties and must therefore be accounted for at all stages of the drug substance and product manufacture as well as the shelf life of the product.…”
Section: Introductionmentioning
confidence: 99%